2009
DOI: 10.1093/eurjhf/hfn040
|View full text |Cite
|
Sign up to set email alerts
|

Immunological mechanisms of pentoxifylline in chronic heart failure

Abstract: The progressive syndrome of chronic heart failure (CHF) represents a common disease pathway that may be derived from a host of varying insults (including myocardial ischaemia and infarction, hypertension, viral infection, pregnancy, etc). Despite this multifarious aetiology, a common phenomena observed in CHF patients is elevated levels of tumour necrosis factor (TNF)‐α. This has led to the widespread concept that TNF‐α is directly involved in the pathophysiology of CHF and as such, attempts have been made to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 44 publications
(44 reference statements)
2
66
0
4
Order By: Relevance
“…Specific inhibitors of this isoenzyme are being developed for use in the treatment of a wide range of disease states with an inflammatory component, including dermatological, neurological and respiratory conditions [38,[41][42][43][44][45][46]. With respect to the reduction in TNF-α by pentoxifylline observed in this study, Shaw [11] has comprehensively reviewed the potential mechanisms which include: Suppression of TNF-α gene transcription by pentoxifylline [47], attenuation of the response of TNF-α to endotoxin [48], and attenuation of Interleukin-2, a cytokine which stimulates TNF-α production [6], Primarily used to treat peripheral arterial disease patients due to the improved circulation obtained through its ability to alter erythrocyte deformability, pentoxifylline also enhances capillary microcirculation [2,11]. We examined the potential of this methylxanthine derivate as a blood pressure (BP) lowering agent in a range of studies, including those that reported its effects in hypertensive patients [20,27] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Specific inhibitors of this isoenzyme are being developed for use in the treatment of a wide range of disease states with an inflammatory component, including dermatological, neurological and respiratory conditions [38,[41][42][43][44][45][46]. With respect to the reduction in TNF-α by pentoxifylline observed in this study, Shaw [11] has comprehensively reviewed the potential mechanisms which include: Suppression of TNF-α gene transcription by pentoxifylline [47], attenuation of the response of TNF-α to endotoxin [48], and attenuation of Interleukin-2, a cytokine which stimulates TNF-α production [6], Primarily used to treat peripheral arterial disease patients due to the improved circulation obtained through its ability to alter erythrocyte deformability, pentoxifylline also enhances capillary microcirculation [2,11]. We examined the potential of this methylxanthine derivate as a blood pressure (BP) lowering agent in a range of studies, including those that reported its effects in hypertensive patients [20,27] .…”
Section: Discussionmentioning
confidence: 95%
“…This is exemplified by increased leukocyte deformability and chemotaxis, decreased endothelial leukocyte 6 adhesion, neutrophil degranulation, TNF-α production and NK cell activity [5,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Pentoxifylline inhibits phosphodiesterase, resulting in an increase of intracellular cyclic adenosine monophosphate activity and down-regulation of pro-inflammatory cytokine synthesis such as TNF-a, IL-6 and interferon-c [9,10]; this drug also inhibits proliferation of peripheral blood mononuclear cell, adherence to the cell matrix and endothelium and T and natural killer cell cytotoxicity [12,19]. Pentoxifylline inhibits synthesis of the inflammation markers at a transcriptional level [9,10], which may represent an advantage over other anti-cytokine drugs, for example etanercept, which only stabilizes TNF-a and hence leads to accumulation in peripheral circulation [20].…”
Section: Discussionmentioning
confidence: 99%
“…A pentoxifilina apresenta como propriedades antiinflamatórias o bloqueio da transcriptase do TNF-α e a redução dos níveis de interleucinas 2 e 6, com consequente redução dos efeitos de cardioagressão dessas citocinas 117 . Na cardiomiopatia dilatada com IC crônica e na cardiomiopatia periparto, a utilização de pentoxifilina na posologia de 1200mg a 2400mg/dia, pelo período de seis meses, ocasionou melhora clínica da classe funcional e da função ventricular (tabela 15).…”
Section: Imunomodulaçãounclassified